Design and construction of a water supply tunnel under New York Harbor, USA. Issue 4 (22nd June 2020) - Watson, David; Lawrence, Colin; Essex, Randall; Shultz, Michael; Larsen, Brian
Abstract : A new water main siphon tunnel was built under New York Harbor in 2015 to allow larger ships to access the Port of New York and New Jersey. Located between Brooklyn and Staten Island, the 2.9 km long 3.6 m dia. tunnel was constructed under active shipping channels through highly variable ground conditions, ranging from decomposed rock to soft clays, all under hydrostatic pressures up to 4 bar beneath the harbour. In a first for New York City, an earth-pressure-balance tunnel boring machine was used. This paper describes the many challenges that faced the project, including a sinkhole forming at the launch and being flooded with sea water for 18 months following hurricane Sandy.